Sequence of Activities on the Exploration of Cassiterite in the Light of the Science, Technology, Society and Environment Approach - Krüger, Joelma Goldner; Terra, Vilma Reis; Campos, Carlos Roberto Pires (Electronic Journal "Fórum Ambiental da Alta Paulista", 2023)
The purpose of this study was to examine the results of a sequence of activities to discuss the exploitation of cassiterite on indigenous lands with regard to education for sustainability, based on the postulates of the Science, Technology, Society and Environment approach (AIKENHEAD, 2005, 2009; AULER, SANTOS, 2011), with the systematization of the sequence of activities based on the proposal of the three pedagogical moments (DELIZOICOV, ANGOTTI, PERNAMBUCO, 2011) in a first year high school class, in the subject of Chemistry at a public school in the state of Espírito Santo/Brazil. This is a qualitative case study, using systematic observation to collect data (GIL, 2022), analyzed in the light of Bardin (2011). The magnitude of the study lies in the fact that there are few studies contributing to its originality. The research contributed to offering a proposal for pedagogical practice with a sustainable perspective in science teaching, going through debates on scientific, technological, social and environmental aspects. As a result, moments of debate situations were provided that fostered an interdisciplinary approach, enabling students to advance in their understanding of the importance of mining in a sustainable and responsible way.